Effectiveness of Using Digital-Based Interactive Media in Improving Fifth Grade Elementary School Students' English-Speaking Skills - Rizqy Amelia Ramadhaniyah Ahmad; Muhamad Alfi Khoiruman; Uslan Uslan (PT. Global Research Collaboration, 2026)
This study investigates the effectiveness of digital-based interactive media in improving English-speaking skills among fifth-grade elementary school students. Previous studies have widely discussed the use of digital media in language learning; however, limited research has specifically examined its impact on elementary-level speaking skills through experimental approaches focusing on pronunciation, fluency, vocabulary, and confidence simultaneously. In addition, many earlier studies emphasized secondary or higher education contexts, leaving a research gap regarding the effectiveness of interactive digital tools for young learners in elementary schools. To address this gap, the present study employed a quasi-experimental design involving 60 fifth-grade students divided into an experimental group and a control group. The experimental group received instruction using digital-based interactive media, while the control group was taught using conventional teaching methods. Data were collected through pre-test and post-test assessments. The findings revealed a substantial improvement in the experimental group, with the mean score increasing from 62.4 to 81.7, while the control group improved from 63.1 to 70.5. An independent samples t-test showed a statistically significant difference between the two groups (p < 0.05). The results indicate that digital-based interactive media significantly enhance students’ speaking performance, engagement, and motivation. This study contributes to the growing body of literature by providing empirical evidence on the effectiveness of interactive digital learning tools for improving English-speaking skills among elementary school learners.